2020
DOI: 10.4274/tjod.galenos.2019.76300
|View full text |Cite
|
Sign up to set email alerts
|

A spontaneous heterotopic pregnancy presenting with acute abdomen treated with natural orifice transluminal endoscopic surgery procedure: Case report

Abstract: Heterotopik gebelik 1/30000 oranında görülür. Bu olguda hasta rüptüre ektopik komponent sebebi ile oluşan akut batın ile başvurmuştur. Hastanın bilinen bir risk faktörü olmaması tanıyı olduğundan daha zor hale getirmiştir. Hasta ve eşinin intrauterin gebeliği koruma istemi mevcut idi. Hasta bu alanda yeni bir minimal invaziv operasyon tekniği olan doğal orifis ile transluminal endoskopik cerrahi prosedürü ile opere edildi. Post-op 1. günde canlı intrauterin gebelikle taburcu edildi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In 2005, Ghezzi et al [ 14 ] reported a single-port laparoscopic salpingectomy for EP. Keziban et al [ 15 ] reported a spontaneous heterotopic pregnancy presenting as an acute abdomen, which was successfully treated using vaginal natural orifice transluminal endoscopic surgery (vNOTES). vNOTES has shown promise in treating various adnexal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, Ghezzi et al [ 14 ] reported a single-port laparoscopic salpingectomy for EP. Keziban et al [ 15 ] reported a spontaneous heterotopic pregnancy presenting as an acute abdomen, which was successfully treated using vaginal natural orifice transluminal endoscopic surgery (vNOTES). vNOTES has shown promise in treating various adnexal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with existed case reports and case-series studies, this study could provide a relatively higher level of evidence for clinician to choose laparoscopic surgery for those patients with HP. Besides, this study could provide some insight to focus on the efficacy and safety of different types of laparoscopy, such as a natural orifice transluminal endoscopic surgery (NOTES) reported in a case report ( 39 ), in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data reported a similarity in terms of intrauterine pregnancy after 24 months and 2-year recurrency of ectopic pregnancy. However, the persistency of trophoblast was 1.8% for salpingectomy and 12% for salpingostomy [12].…”
Section: Introductionmentioning
confidence: 93%